2018
DOI: 10.1007/978-3-319-99046-0_30
|View full text |Cite
|
Sign up to set email alerts
|

Trade-Off Between Work and Correlations in Quantum Thermodynamics

Abstract: Quantum thermodynamics and quantum information are two frameworks for employing quantum mechanical systems for practical tasks, exploiting genuine quantum features to obtain advantages with respect to classical implementations. While appearing disconnected at first, the main resources of these frameworks, work and correlations, have a complicated yet interesting relationship that we examine here. We review the role of correlations in quantum thermodynamics, with a particular focus on the conversion of work int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 58 publications
(96 reference statements)
1
23
0
Order By: Relevance
“…Several works address the influence of coherence [12,14,15,27,28] and correlations [7,19,[29][30][31][32][33][34][35][36][37][38] in thermodynamic transformations in different scenarios. In * cerisola@df.uba.ar † augusto@df.uba.ar general, the creation of correlations is associated to some energetic cost and strategies to optimally extract work from them have been put forward [33][34][35][36][37][38]. On the other hand, it has been demonstrated that in the single-shot regime, by allowing auxiliary correlated catalytic systems [7] or correlations with catalytic systems [19], it is possible to enlarge the set of achievable transformations.…”
Section: Introductionmentioning
confidence: 99%
“…Several works address the influence of coherence [12,14,15,27,28] and correlations [7,19,[29][30][31][32][33][34][35][36][37][38] in thermodynamic transformations in different scenarios. In * cerisola@df.uba.ar † augusto@df.uba.ar general, the creation of correlations is associated to some energetic cost and strategies to optimally extract work from them have been put forward [33][34][35][36][37][38]. On the other hand, it has been demonstrated that in the single-shot regime, by allowing auxiliary correlated catalytic systems [7] or correlations with catalytic systems [19], it is possible to enlarge the set of achievable transformations.…”
Section: Introductionmentioning
confidence: 99%
“…To formulate our ideas we adopt a commonplace view in quantum thermodynamics, namely, that work is a central resource that is required to move systems away from freely available thermal equilibrium states [24]-an approach that has staged a diverse range of investigations within the broader field [25][26][27]. In this paradigm, previous research has investigated the work-cost (or gain) of quantum processes [28][29][30][31][32], refrigeration [33,34], or for establishing correlations [35][36][37][38].…”
Section: Tpm Schemementioning
confidence: 99%
“…2. These five points are A =p (1, 1, 1) , B =p (7, 1, 1) , C =p (13,7,1) , D =p (9,7,1) , and E =p since p 0 (β) ≥ p 1 (β) and p 0 (β) + p 1 (β) ≥ 1 2 for any Hamiltonian and any temperature. This means the point (0, y(β), z(β)) is contained in polytope since it can be obtained as a convex combination of A and B.…”
Section: Axii Geometry Of Equal Thermal Marginals For Two Ququartsmentioning
confidence: 99%
“…Here, we explore the specific quantitative relation between correlations and energy [7]. While general qualitative insights can help to understand some quandaries arising from Maxwell's demon or Szilard's engine [8][9][10], and correlations play various interesting roles in quantum thermodynamics (see, e.g., [2,3,[11][12][13][14][15][16][17][18]), precise quantitative statements about the trade-off between work and correlations are generally complicated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation